Howzat! Navigating Gender Disruptions in Australian Young Women's Cricket. Issue 1 (2nd January 2019) - Mooney, Amanda; Hickey, Chris; Ollis, Debbie; Harrison, Lyn
ABSTRACT: "Howzat" is colloquially used by cricketers to ask the umpire "How is that?" when they believe a batter is out. We employ this question here to frame interrogations of young women's experiences as they navigate elite pathway cricket in an era of significant change. The global sports entertainment industry is, it seems, undergoing a form of gender disruption. The remuneration for Australian women cricketers rose by over 500 per cent between 2012 and 2017, providing opportunities for women and girls to transition to professional sport in ways quite different from historical amateur pathways. While on the surface this shapes as a time of great opportunity for aspiring sportswomen, there are unintended consequences that warrant consideration—particularly for females involved in sports with a legacy of masculine privilege. This article draws on qualitative research concerning five female pathway players and their respective parents, coaching and administrative staff who support them as they navigate the demands of playing elite cricket during adolescence. We employ Foucault's concept of a "history of the present" to make sense of this dispositif to problematise how young women navigate gendered experiences in sports with "masculine" traditions amid a growing profile of women's sport in Australia.